Molecular mechanism of acetylsalicylic acid in improving learning and memory impairment in APP/PS1 transgenic mice by inhibiting the abnormal cell cycle re-entry of neurons - Guan, Pei-Pei; Ding, Wei-Yan; Wang, Pu (Frontiers in Molecular Neuroscience, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder accompanied by the loss and apoptosis of neurons. Neurons abnormally enter the cell cycle, which results in neuronal apoptosis during the course of AD development and progression. However, the mechanisms underlying cell cycle re-entry have been poorly studied. Using neuroblastoma (N) 2aSW and APP/PS1 transgenic (Tg) mice as in vitro and in vivo AD models, we found that the expression of cyclin-dependent kinase (CDK)1/2/4 and cyclin A2/B1/D3/E1 was increased while the protein expression of p18 and p21 was decreased, which led to enhanced cell cycle re-entry in a β-amyloid protein (Aβ)-dependent mechanism. By preparing and treating with the temperature-sensitive chitosan-encapsulated drug delivery system (CS), the abnormal expression of CDK1/2/4, cyclin A2/B1/D3/E1 and p18/21 was partially restored by acetylsalicylic acid (ASA), which decreased the apoptosis of neurons in APP/PS1 Tg mice. Moreover, CDK4 and p21 mediated the effects of ASA on activating transcription factor (TF) EB via peroxisome proliferator-activated receptor (PPAR) α, thus leading to the uptake of Aβ by astrocytes in a low-density lipoprotein receptor (Ldlr)-dependent mechanism. Moreover, the mechanisms of Aβ-degrading mechanisms are activated, including the production of microtubule-associated protein light chain (LC) 3II and Lamp2 protein by ASA in a PPARα-activated TFEB-dependent manner. All these actions contribute to decreasing the production and deposition of Aβ, thus leading to improved cognitive decline in APP/PS1 Tg mice.